Data Integration of Health Financing Systems as a Critical Enabler for Objective-Oriented Health System Reform: A Scoping Review from India - Grace Achungura; Arif Raza; Vijendra Katre; Jaidev Singh Anand; Nirmala Ravishankar; Rathan Kelkar (Health Systems & Reform)
Health financing fragmentation poses a challenge to reforms intended to address system-wide objectives vis-à-vis universal health coverage (UHC). India’s experience with publicly subsidized health insurance schemes (PSHIs), such as Rashtriya Swasthya Bima Yojana (RSBY) and its state adaptations, testify to the challenges inherent in effecting objective-oriented health systems reforms, particularly owing to wide variation in programmatic and operational design. Recent efforts to defragment PSHIs under the aegis of a new government initiative called Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (PMJAY) using, inter alia, a unified information and communication technology (ICT) interface provide important policy lessons. This paper presents a theory of change for the role that ICT systems can play in promoting the objectives of UHC and highlights the early effects of ICT reforms in India on UHC. Holistic and defragmented ICT systems have a positive effect on the processes and operations of government health programs, according to the literature reviewed. Streamlined ICT systems promote equity through the introduction of portability modules, which increase access to services and facilitate stronger transparency and accountability measures by using big data and machine learning for fraud detection. Although reliability issues persist on certain fronts, India’s experience with homegrown, incremental reforms to defragment ICT systems for health financing have proven of paramount importance for progressing toward UHC.